Textured CH3NH3PbI3 thin film with enhanced stability for high performance perovskite solar cells. (March 2017) - Long, Mingzhu; Zhang, Tiankai; Zhu, Houyu; Li, Guixia; Wang, Feng; Guo, Wenyue; Chai, Yang; Chen, Wei; Li, Qiang; Wong, Kam Sing; Xu, Jianbin; Yan, Keyou
Abstract: MAPbI3 perovskite is an important component for high-performance perovskite solar cell (PSC) but its own thin film stability is challenging in PSC community. Herein, we report a high crystallinity perovskite MAPbI3 with texture structure prepared from HPbI3 reacted with low partial pressure (LPP) MA gas, that has substantially higher both thermal and moisture stability than polycrystalline perovskite (PP) prepared from MAI+PbI2 . A prototype reactor is developed to perform coordination engineering between MA vapor and HPbI3 solid and facilitate the large-scale fabrication. The large Pb-N binding energy (~80.04 kJ mol −1 ) results in the liquefied state after MA adhesion. Finally, a high texture perovskite (TP) is formed after excess MA expeditious releasing. The MA-rich passivation through Pb-N bonding at interface and boundary contributes to the substantial improved stability. Besides, MA-rich species trigger an anti-degradation reaction in presence of moisture and thus endow stability above two months under ~65% humidity. The textured PSCs (TPSCs) deliver power conversion efficiency (PCE) between 15.5% and champion 18.9% in the batch deposition. Therefore, the coordination engineering improves the efficiency, stability, scalability and ease of fabrication together. Graphical abstract: A texture perovskite (TP) MAPbI3 thin film was developed through the reaction between diluted MA vapor and HPbI3 solid. The XRD intensity of the prepared perovskite without annealing generally can be as high as 10 6 to 10 7 which is rarely reported. The high crystallinity of TP is attributed to the excess MA strongly coordinating to Pb (II) and crosslinking adjacent crystals. This excess MA can passivate perovskite surface and grain boundary, leading to 2 months stability under 65% humidity and also substantially improved thermal stability. And the texture perovskite delivered champion PCE 18.9% in the batch production. Therefore, the excess MA coordination in the TP is beneficial for the crystallinity, PCE, stability and scalability together.